Access and Use of Device‐Aided Therapies for Parkinson's Disease in Denmark. Issue 6 (2nd July 2020) - Henriksen, Tove; Dalhoff, Kim Peder; Hansen, Henriette Engel; Brenneche, Andreas W.; Lønberg, Ulla Sofie; Danielsen, Erik Hvid
Abstract: Background: In Denmark's five regions, there is potential inequality in access to device‐aided therapy (DAT) for Parkinson's disease (PD) based on structural or socioeconomic factors. It is unclear how long DAT is maintained and affects concomitant medication. Objectives: To investigate access to DAT by comparing the proportion of patients with DBS, subcutaneous apomorphine infusion (SCAI), or levodopa/carbidopa intestinal gel (LCIG) in Danish regions 2008–2016 and describe demographics of patients, changes in use of comedication, and maintenance of DAT. Methods: This work is a retrospective nationwide population‐based registry analysis generated by combining various registries and statistics in Denmark. Results: From 2008 to 2016, 612 patients started DAT. There were statistically significant differences in the number of patients starting DAT between the Capital Region (99.5 per 1, 000) and both Central Jutland (66.6 per 1, 000) and North Jutland (70.6 per 1, 000; P  < 0.05). Among DBS and LCIG patients, respectively, 4% and 42% were aged ≥70 years, 68% and 63% were men (vs. 59% in the general PD population; P  < 0.05 for DBS), 73% and 63% had a partner (vs. 62% in the general PD population), and 73% and 71% had a qualifying education (vs. 63% in the general PD population; P  < 0.05). Use of PD‐related medication decreased significantly from 4 years before to 4 years after DAT. Eighty‐one percent of the patients who started LCIG, alive 4 years later, had maintained this treatment. Conclusions: There is unequal access to DAT in the Danish regions, and political and social considerations are warranted to address structural and socioeconomic causes.